Ferry Management at Banjar Raya Pelambuan Pier, West Banjarmasin District - Pitriyani Pitriyani; Ersis Warmansyah Abbas; Jumriani Jumriani; Fatwa Nur'aini; Sigit Triyono (The Innovation of Social Studies Journal, 2026)
Ferry Management at Banjar Raya Pier, Pelambuan District, West Banjarmasin This research is based on the important role of ferry management as public transportation, which is still used daily. People use ferries for various purposes such as work, trade, school, and participating in other social activities, especially in areas that are inaccessible by land transportation. The purpose of this study is to determine how the ferry is managed in Banjar Raya. Qualitative methods are used in this study, with the aim of collecting data through observation, interviews, and documentation. The management of the ferry dock, the ship's captain, and ferry passengers at Banjar Raya Pier are the subjects of this research. The data collection techniques include direct observation, in-depth interviews, and documentation. Data analysis is carried out through data reduction stages adjusted to the focus of the study, descriptive data presentation, and drawing conclusions based on field findings. To ensure the validity of the data, the researcher applies triangulation techniques. The results of the study on ferry management at the Banjar Raya Pelambuan pier, West Banjarmasin district, show that ferries continue to be an important means of crossing people and transporting goods for people living along the riverbanks. The conclusion found that ferry management plays an important role as a means of daily mobility and connecting areas separated by rivers, especially without bridges. Ferries facilitate the flow of goods and passengers, support the local economy, operate intensively from morning to night, and provide social benefits and livelihoods for the surrounding community.